Bersama elemen masyarakat menciptakan lingkungan sekolah yang kondusif untuk proses belajar mengajar - Dody Fatkhur; Y. Touvan Juni Samodra (JPPTK: Jurnal Pendidikan Pembelajaran & Penelitian Tindakan, 2021)
In the modern era, the principal required to solve tasks and problems develops the existing potential in the school into something useful for students. The situation at SDN 11 Penyeberang Bala is that there is still much local livestock roaming around the school environment, thus disrupting the teaching and learning process and destroying existing plants in schools. The method to overcome this is by creating a school fence involving the committee and the guardians of the students. The purpose of making this fence is so that livestock does not enter the school environment so that the school environment becomes a comfortable place to study. Thanks to the cooperation of all school members, committees, and student guardians, finally, can create the school fence, and students can learn comfortably.